Stakeholders’ Perceptions of IFSU VMGO, COE VMG, and BEEd Program Objectives - Peter Paul Canuto; Yuvimin Lumidao; Elpidio Jr. Basilio; Marites Choycawen; Deborah Lumecio (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
Universities depend on a coherent framework that offers direction and guide their daily operations. This framework is usually anchored in a clearly articulated vision, mission, goals, and objectives (VMGO), including core values. Their effectiveness, however, are influenced by the stakeholders’ views and experiences, as they are the ones who are most affected. The current undertaking therefore aimed to assess the stakeholders' perceived levels of awareness, understanding, acceptability, relevance, and attainability of the VMGO and the core values of Ifugao State University (IFSU). It included the VMGO of the College of Education (COE) and the Bachelor of Elementary Education (BEEd) Program of the IFSU - Tinoc Campus. The congruence among the university VMGO, college VMG, and program objectives was likewise examined. Using a descriptive research design, the study employed a survey questionnaire to collect quantitative data from the total population of 558 internal and external stakeholders. Results reveal that stakeholders were highly aware and generally perceived the university VMGO and core values, as well as the college VMG and program objectives, as understandable, acceptable, relevant, and attainable. Internal stakeholders consistently reported higher levels of awareness and understanding, while external stakeholders recognized the program's practical alignment with the university's overarching goals. The high level of perceived congruence between the university, college, and program VMGOs demonstrates strong integration and coherence across institutional levels. However, variations in perception underscore the need for continuous evaluation, communication, and integration of stakeholder feedback to enhance institutional effectiveness.